2004
DOI: 10.2746/0425164044890625
|View full text |Cite
|
Sign up to set email alerts
|

Routine castration in 568 draught colts: incidence of evisceration and omental herniation

Abstract: Summary Reasons for performing study: Castration is one of the most common routine surgical procedures performed in the horse, from which a number of potential complications can arise. We undertook a prospective evaluation of short‐term complications associated with castration of draught colts over a 3‐year period (1998–2000). Objectives: To compare castration complications in a large number of draught foals with previously published literature. Methods: Five hundred and sixty‐eight draught colts, age 4 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
4
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 14 publications
3
62
4
12
Order By: Relevance
“…Nesta técnica, a abertura da túnica vaginal acarreta uma comunicação do meio externo com a cavidade abdominal aumentando, assim, o fluxo de ar para o interior da mesma e elevando a sua pressão. A técnica fechada evita esta comunicação (Thomas et al, 1998, Shoemaker et al, 2004, Carmalt et al, 2008.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Nesta técnica, a abertura da túnica vaginal acarreta uma comunicação do meio externo com a cavidade abdominal aumentando, assim, o fluxo de ar para o interior da mesma e elevando a sua pressão. A técnica fechada evita esta comunicação (Thomas et al, 1998, Shoemaker et al, 2004, Carmalt et al, 2008.…”
Section: Discussionunclassified
“…Por outro lado, foi submetido ao decúbito lateral para a realização do Acredita-se que a palpação retal prévia à orquiectomia associado com a palpação dos testículos e bolsa escrotal poderia auxiliar na detecção de um anel inguinal interno dilatado ou qualquer alteração no mesmo, todavia esta prática não é realizada no pré-operatório de orquiectomia na espécie equina, além de não necessariamente indicar ou prever algum problema futuro. Apesar de recomendado, este procedimento apresenta limitações, pois, a padronização do tamanho do anel não está bem discutido na literatura para comparação e ainda torna-se difícil uma determinação exata da largura do anel inguinal detectada na palpação, sendo este dado apenas subjetivo, onde a experiência do cirurgião prevalece (Searle et al, 1999, Shoemaker et al, 2004. No presente relato, não foi realizada a palpação prévia visando detectar alterações prévias no anel inguinal interno, visto que o animal era saudável, com histórico de coberturas durante sua vida reprodutiva, sem quaisquer intercorrências.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Although age and breed traditionally have not been related with higher predispositions, several authors have reported a higher prevalence in different breeds (Mezerova et al, 2003;Shoemaker et al, 2004).…”
mentioning
confidence: 99%